2021
DOI: 10.29130/dubited.815454
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Body Fat Percentage Using Support Vector Machine and Random Forest Methods

Abstract: Obezite, önemli bir sağlık problemidir ve yaygınlığı giderek artmaktadır. Bu hastalığın, diğer birçok hastalığın tetikleyicisi ve habercisi olduğu bilinmektedir. Obezite hastalığının tedavi sürecinden önce, vücut yağ yüzdesinin doğru bir şekilde tespit edilmesi önemlidir. Yüksek maliyetli yöntemler ile vücut yağ yüzdesi kesin olarak ölçülmektedir. Bu çalışmada, kişilerden alınan antropometrik veri seti ile vücut yağı yüzdesi tespitinin doğru ve maliyetsiz bir şekilde tahmin edilebilmesi için destek vektör regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…As a result of the literature review, studies examining the effect of capital structure on financial performance are " ; ; Çanakçıoğlu and Ersan (2020); Özdemir (2019); Le and Phan (2017); Akpinar (2016); ; ; ; ; ; Nirajini and Priya (2013); ; Salim and Yadav (2012); ; ; ; ; "; studies examining the effect of debt financing on financial performance are " Ophelia et al (2021); ; ; ; Muchugia (2013); Obert and Olawale (2010)"; studies examining the effect of debt structure on asset profitability are " Baraklı and Öndeş (2021); Say and Doğan (2022); " has been examined extensively in national and international literature. Additionally, in the study conducted by "Chen (2012)" in the literature, the relationship between board structure, cost of debt and firm performance was examined; in the study conducted by ", the relationship between government subsidies, cost of debt and firm performance was examined, and in the study conducted by "Özer, Çam and Cookie (2023)", the relationship between corporate governance and cost of debt was examined.…”
Section: Literature On Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the literature review, studies examining the effect of capital structure on financial performance are " ; ; Çanakçıoğlu and Ersan (2020); Özdemir (2019); Le and Phan (2017); Akpinar (2016); ; ; ; ; ; Nirajini and Priya (2013); ; Salim and Yadav (2012); ; ; ; ; "; studies examining the effect of debt financing on financial performance are " Ophelia et al (2021); ; ; ; Muchugia (2013); Obert and Olawale (2010)"; studies examining the effect of debt structure on asset profitability are " Baraklı and Öndeş (2021); Say and Doğan (2022); " has been examined extensively in national and international literature. Additionally, in the study conducted by "Chen (2012)" in the literature, the relationship between board structure, cost of debt and firm performance was examined; in the study conducted by ", the relationship between government subsidies, cost of debt and firm performance was examined, and in the study conducted by "Özer, Çam and Cookie (2023)", the relationship between corporate governance and cost of debt was examined.…”
Section: Literature On Researchmentioning
confidence: 99%
“…As a result of evaluating the literature as a whole, it was determined that regression analysis was used in the studies. Some of the studies examining the effect of capital structure, debt financing and debt structure on financial performance include positive results that are " Baraklı and Öndeş (2021); ; ; Muchugia (2013); Nirajini and Priya (2013); " and some studies including " Say and Doğan (2022); ; Ngoc,Tien and Thu (2021); Ophelia et al (2021); Çanakçıoğlu and Ersan (2020); Özdemir (2019); ; Le and Phan (2017); ; ; ; ; Salim and Yadav (2012); " were obtained negative results. In some studies, " ; Obert and Olawale (2010) it was found that capital structure; debt financing and debt structure do not have a significant effect on financial performance.…”
Section: Literature On Researchmentioning
confidence: 99%